Post-COVID-19 impairment of the senses of smell, taste, hearing, and balance - Ludwig, Sonja; Schell, Angela; Berkemann, Michelle; Jungbauer, Frederic; Zaubitzer, Lena; Huber, Lena; Warken, Christian; Held, Valentin; Kusnik, Alexander; Teufel, Andreas; Ebert, Matthias; Rotter, Nicole (Viruses, 2022)
Background: Various symptoms have been associated with COVID-19, but little is known about the impacts of COVID-19 on the sensory system, risk factors, and the duration of symptoms. This study assesses olfactory, gustatory, hearing, and vestibular systems after COVID-19. Methods: This cross-sectional, single-center study involved 50 patients one to six months after COVID-19 and reports their patient records and the extent, onset, and duration of olfactory, gustatory, hearing, and balance disorders using questionnaires during and after COVID-19. Sensory symptoms were objectively studied using the following clinical tests after COVID-19 Sniffin’ Sticks, taste tests, tone/speech audiometry, and video head impulse test. Results: Post-COVID-19-patients were suffering from olfactory and gustatory impairment for up to six months. According to the Dizziness Handicap Inventory, balance disorders were less noticed: Overall, about 40% of the patients during COVID-19 and nearly all patients recovered within six months. After COVID-19, clinical tests revealed that 75% were suffering from hyposomnia/anosmia, and 20% of all patients reported mild hypogeusia for up to six months. Vestibular disorders and hearing impairment rarely/did not occur. Females were significantly more affected by sensory impairments than males. Conclusions: COVID-19 particularly caused olfactory and gustatory impairment; balance disorders were present too; vestibular and auditory symptoms were negligible.